Cryogenic 35 GHz pulse ENDOR probehead accommodating large sample sizes: Performance and applications - Tschaggelar, Rene; Kasumaj, Besnik; Santangelo, Maria Grazia; Forrer, Joerg; Leger, Patrik; Dube, Henry; Diederich, Francois; Harmer, Jeffrey; Schuhmann, Rolf; Garcia-Rubio, Ines; Jeschke, Gunnar (Journal of Magnetic Resonance, 2009)
The construction and performance of a cryogenic 35 GHz pulse electron nuclear double resonance (ENDOR) probehead for large samples is presented. The resonator is based on a rectangular TE102 cavity in which the radio frequency (rf) B2-field is generated by a two turn saddle ENDOR coil crossing the resonator along the sample axis with minimal distance to the sample tube. An rf power efficiency factor is used to define the B2-field strength per square-root of the transmitted rf power over the frequency range 2-180 MHz. The distributions of the microwave B1- and E1-field, and the rf B2-field are investigated by electromagnetic field calculations. All dielectrics, the sample tube, and coupling elements are included in the calculations. The application range of the probehead and the advantages of using large sample sizes are demonstrated and discussed on a number of paramagnetic samples containing transition metal ions. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-04-02
Keywords: ENDOR; ENDOR resonator; Large sample resonator; Pulse EPR; Q-band probehead